Interleukin-17 modulates uPA and MMP2 expression in human periodontal ligament mesenchymal stem cells: involvement of the ERK1/2 MAPK pathway - Okić Đorđević, Ivana; Kukolj, Tamara; Obradović, Hristina; Trivanović, Drenka; Petrović, Andjelija; Mojsilović, Slavko; Miletić, Maja; Bugarski, Diana; Jauković, Aleksandra (Archives of Biological Sciences, 2022)
Paper description: Proinflammatory cytokine IL-17 regulates the expression of extracellular proteolytic enzymes in multiple cell types. We investigated whether it contributes to periodontal ligament remodeling and tissue destruction. The influence of IL-17 on urokinase-type plasminogen activator (uPA) and metalloproteinase (MMP) MMP2/MMP9 gene and protein expression in periodontal ligament mesenchymal stem cells (PDLMSCs) was investigated by RT-PCR, Western and zymography analyses. IL-17 stimulates uPA and matrix MMP-2 gene and protein expression through activation of the extracellular signal-regulated kinase (ERK)1/2 mitogen-activated protein (MAP) kinase signaling pathway. IL-17 contributes to extracellular degradation in the periodontal ligament and it could be involved in periodontal disease pathogenesis. Abstract: Periodontal disease is a chronic infection of periodontal tissue characterized by extracellular matrix (ECM) degradation due to increased expression of plasminogen activators and matrix metalloproteinases (MMPs) and various proinflammatory cytokines, including interleukin (IL)-17. Successful regeneration of damaged periodontal tissues depends on the proper functionality of periodontal ligament mesenchymal stem cells (PDLMSCs), especially the production of extracellular matrix proteases. We investigated the influence of IL-17 on ECM remodeling through modulation of urokinase-type plasminogen activator (uPA) and MMP2/MMP9 expression in human PDLMSCs at mRNA, protein and activity levels using by RT-PCR, Western blotting and zymography, respectively. Investigation of the involvement of MAPKs in these processes in PDLMSCs was determined by Western blotting, as well as by utilizing specific p38 and MEK1/2 inhibitors. Our results show that IL-17 activates MAPK signaling in PDLMSCs. Moreover, IL-17 had no effect on MMP9 expression, but it stimulated uPA and MMP2 gene and protein expression in PDLMSCs through the activation of the ERK1/2 MAPK signaling pathway. The obtained data suggest that IL-17 contributes to ECM degradation in the periodontal ligament by stimulating uPA and MMP2 expression and activity in PDLMSCs. This information is important for understanding periodontal disease development and defining future directions of its treatment.